Establishment of a New Cell Line of Canine Mammary Tumor CMT-1026 - Mei, Chen; Xin, Liang; Liu, Yang; Lin, Jiabao; Xian, Hong; Zhang, Xue; Hu, Wei; Xia, Zhaofei; Wang, Hongjun; Lyu, Yanli (Frontiers in Veterinary Science, 2021)
Canine mammary tumors (CMTs) have histopathological, epidemiologic and clinical characteristics similar to those in humans and are known to be one of the best models for human breast cancer (HBC). This research aimed to describe a newly established canine cell line, CMT-1026. Tumor samples were collected from a female dog exhibiting clinical mammary neoplasm, and the adherent cells were cultured. Both the histology and immunohistochemistry (IHC) of tumor samples were estimated. Cell growth, ultrastructural, cytological and immunocytochemistry (ICC) features of CMT-1026 were examined. CMT-1026 cells were inoculated into ten female BALB/c nude mice to evaluate oncogenicity and metastatic ability. Hematoxylin-eosin (H.E.) staining of the tumors revealed an epithelial morphology. Electron microscopy was used to detect histological and cytological of smears, and ultrathin sections showed that CMT-1026 cells were polygonal and characterized by atypia and high mitotic index in the tumor, with prominent nucleoli and multinucleated cells. IHC characterization of CMT-1026 indicated ER-, PR-, HER-2, p63+, CK5/6+ and α-SMA+ epithelial cells. ICC characterization of CMT-1026 showed high expression of Claudin-1, Delta-catenin, SOX-2 and KI-67. At 2 weeks after inoculation of the CMT-1026 cells, phyma was found in 100% of the mice. The xenograft cancers showed conservation of the original H.E. features of the female dog cancer. In conclusion, CMT-1026 may be a model of canine mammary cancer that can be used in research on the pathogenesis of both CMT and HBC.